Aplicações toxicogenômicas em cultura de células expostas a nanomateriais e populações humanas expostas a pesticidas - Franco, Fernanda Craveiro (2017)
The interaction of some compounds and DNA molecule can cause genotoxic changes. The tests used to evaluate genotoxicity have evolved over the years, and they have great efficiency. Currently, several traditional methodologies are used, such as the comet assay, and some more modern, based on molecular biology. Considering the importance of detecting the effects caused by exposure to potentially genotoxic agents, this thesis presents three chapters with different approaches to this topic. The first chapter aimed at evaluating published studies on the mutagenic, genotoxic and oxidative effects caused by occupational exposure to pesticides. For this, a systematic review of articles published between the years of 2011 and 2015 was carried out, focusing on these exposure conditions. The results showed that 44% of the studies addressed only men and 44% approached men and women, and 78% used rural workers as an exposed population. The most evaluated class of pesticide was organophosphorus. The studies were separated by methodologies of analysis used and all showed some type of alteration in the populations occupationally exposed to pesticides. The second chapter, published in the journal Environmental Science and Pollution Research, considered the dengue scene in the state of Goias and techniques of mosquitoes control, and sought to understand the genotoxic effects caused by exposure of endemic agents to pesticides used against Aedes aegypti, being the first study published with this group of workers. The main pesticides used were insecticides and larvicides and an increase in DNA damage was observed in the exposed population, without influence of the lifestyle factors. In the whole transcriptome assay the differential expression of genes related to various chronic diseases was observed. Finally, the third chapter was carried out in collaboration with the Institute of Experimental Medicine of the Czech Academy of Sciences, aiming the determination of cytotoxic and genotoxic effects caused by in vitro exposure to different types of metallic nanomaterials. In nanomaterials that showed cell viability reduction (cytotoxic), an increase in genotoxicity was also identified. In addition, three of the four non-cytotoxic nanomaterials evaluated showed genotoxic effects. Studies aimed at detecting the compounds genotoxic potential are extremely important for the regulatory definition and identification of risks caused by exposure. In this study, the toxicological and genotoxic effects of different compounds and mixtures were evaluated using traditional and modern techniques, in vitro or by human biomonitoring, seeking to understand and determine the risks involved in exposure to these substances.